2000
DOI: 10.1046/j.1365-2257.2000.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

The determination of a reference range for new platelet parameters produced by the Bayer ADVIATM 120 full blood count analyser

Abstract: One hundred and twenty-two samples from normal volunteers were processed for full blood count analysis through the Bayer ADVIA120. The samples were simultaneously tested using the marker CD62P to establish the absence of platelet activation. Samples were tested at two time intervals, 20 min and 3.5 h, to simulate the testing practice for routine and urgent samples in our laboratory. From these data the mean and reference ranges, with 95% confidence limits, for platelet parameters were calculated for the ADVIA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 7 publications
5
30
2
2
Order By: Relevance
“…In this study, it was found that the platelet-derived indices of mean platelet volume, platelet distribution width, and platelet-large cell ratio show significantly high values for cases of ITP compared with hypoproductive type. The sensitivity, specificity, positive p-value, and the negative p value of the platelet-derived indices were appropriate for differentiating between thrombocytopenias due to platelet destruction (ITP) and low platelet production as was observed in studies carried out by Bowles et al; 10 Lee WS; 11 Briggs C; 12 Farias; 13 Brummitt; 14 Lanzkowsky P. 15 In the present study average MPV for Controls was 9. In the present study, the P-LCR was significantly higher in ITP patients compared with the control group and significantly lower in hypoproductive thrombocytopenia patients compared with the control group.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, it was found that the platelet-derived indices of mean platelet volume, platelet distribution width, and platelet-large cell ratio show significantly high values for cases of ITP compared with hypoproductive type. The sensitivity, specificity, positive p-value, and the negative p value of the platelet-derived indices were appropriate for differentiating between thrombocytopenias due to platelet destruction (ITP) and low platelet production as was observed in studies carried out by Bowles et al; 10 Lee WS; 11 Briggs C; 12 Farias; 13 Brummitt; 14 Lanzkowsky P. 15 In the present study average MPV for Controls was 9. In the present study, the P-LCR was significantly higher in ITP patients compared with the control group and significantly lower in hypoproductive thrombocytopenia patients compared with the control group.…”
Section: Discussionmentioning
confidence: 64%
“…Because of our original inclusion criteria (patients who underwent PCI and for whom hsCRP levels and MPV were measured), a selection bias is possible. Moreover, MPV increases with increasing storage duration in EDTA, and the outcomes become more and more untrustworthy after 4 h [35,36]. However, the MPV Outcome prediction by hsCRP and MPV after PCI Moon et al 75 Log-rank < 0.0001…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, patients with acute MI have lower MPG than those with unstable angina (17). However, as MPM and MPG are not derived directly (26,27), some degree of caution in interpretation is required, as inter-relationships may be more mathematic than physiologic. The inverse correlation between MPG (granularity) and MPV (volume) in the controls (i.e., in health) implies that large platelets have reduced granularity, and notably, this relationship is not present in the entire patient cohort.…”
Section: Discussionmentioning
confidence: 97%